CATEGORY SHIFT ANALYSIS IN THE BILINGUAL INFORMATION BOARDS AT MUSEUM SANDI YOGYAKARTA - Ahmad Misbahul; Tri Septa Nurhantoro; Apriliana Hapsari (JOLALI: Journal of Language and Literature, 2023)
Bilingual information has an important role in bridging communication from one language to another, and this also happens in the tourism field. Currently, the Indonesian government is making tourism as one of the primary sectors in increasing state income. Since there is the importance of bilingual information, this research proposes to examine the quality of the translation of the bilingual information boards at Museum Sandi and describe the relationship between category shifts and the quality of the degree of equivalence meaning. The research employed a qualitative descriptive method in discussing the types of category shifts and the degree of quality equivalence meaning on the bilingual information board. This research classified types of category shift and meaning equivalence of translation found in the translated text into the columns and presented the data in the form of numbers and percentages. This research shows that the category shift occurring in bilingual information boards at Museum Sandi Yogyakarta is still relevant and understandable for foreign tourists.